2003
DOI: 10.1002/jqs.756
|View full text |Cite
|
Sign up to set email alerts
|

Glacier variations in Breheimen, southern Norway: dating Little Ice Age moraine sequences at seven low‐altitude glaciers

Abstract: 2003. Glacier variations in Breheimen, southern Norway: dating Little Ice Age moraine sequences at seven low-altitude glaciers.ABSTRACT: Moraine sequences in front of seven relatively low-altitude glaciers in the Breheimen region of central southern Norway are described and dated using a 'multi-proxy' approach to moraine stratigraphy. Lichenometric dating, based on the Rhizocarpon subgenus, is used to construct a composite moraine chronology, which indicates eight phases of synchronous moraine formation: AD . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 49 publications
5
35
1
1
Order By: Relevance
“…The Holocene glacial history obtained in this study deviates in some periods with that suggested for northern Sweden (Karlén, 1973;Karlén and Denton, 1975;Karlén, 1976) and for northern Norway (Griffey and Worsley, 1978;Ballantyne, 1990;Winkler et al, 2003 …”
Section: Comparison With Holocene Glacier Records In Northern Scandincontrasting
confidence: 76%
See 3 more Smart Citations
“…The Holocene glacial history obtained in this study deviates in some periods with that suggested for northern Sweden (Karlén, 1973;Karlén and Denton, 1975;Karlén, 1976) and for northern Norway (Griffey and Worsley, 1978;Ballantyne, 1990;Winkler et al, 2003 …”
Section: Comparison With Holocene Glacier Records In Northern Scandincontrasting
confidence: 76%
“…Similar measurements on the M10 and M8 moraines yield maximum lichen diameters >230 and >250 mm, respectively, that are well beyond the realible range of modern growth curves in Norway (e.g. Innes, 1985;Matthews, 1994;Winkler et al, 2003).…”
Section: Frost Polygonsmentioning
confidence: 59%
See 2 more Smart Citations
“…The Schmidt hammer can be used as part of a "multiproxy approach" with lichenometry and (if possible) radiocarbon dating of associated deposits (Winkler et al 2003). Lichenometry has the potential to date moraines with a precision of up to 5-10 yr, but cannot be used for dates extending further back than c. 500 yr (Innes 1985;Matthews 1994).…”
Section: Introductionmentioning
confidence: 99%